2021
DOI: 10.3390/jcm10194558
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Impulsivity, Hyperactivity, and Inattention and the Association with Mental Health and Substance Use Severity in Opioid-Dependent Patients Seeking Treatment with Extended-Release Naltrexone

Abstract: The level of impulsivity, hyperactivity, and inattention (IHI) is higher among patients with substance use disorder (SUD) than in the general population. However, the prevalence of such symptoms in patients seeking treatment with an opioid antagonist, such as extended-release naltrexone (XR-NTX), is unknown. We screened 162 patients with opioid use disorder (OUD) seeking treatment with XR-NTX in Norway using the Adult ADHD Self-Report Scale (ASRS) to estimate the prevalence of IHI alongside an assessment of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Leong's findings may indicate that ILF-NF targets the underlying urge to use drugs (i.e., the craving mechanism), to which restlessness may be a contributing factor, as well as the ability to control these impulses. 19,42,43 Previous studies have shown positive results from neurofeedback in individuals with attention-deficit/hyperactivity disorder and attentional deficits. 44 Whereas our sample was drawn from an unselected drug-using population, other studies have focused more narrowly on selected subpopulations of substance users and, therefore, had a more homogeneous patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…Leong's findings may indicate that ILF-NF targets the underlying urge to use drugs (i.e., the craving mechanism), to which restlessness may be a contributing factor, as well as the ability to control these impulses. 19,42,43 Previous studies have shown positive results from neurofeedback in individuals with attention-deficit/hyperactivity disorder and attentional deficits. 44 Whereas our sample was drawn from an unselected drug-using population, other studies have focused more narrowly on selected subpopulations of substance users and, therefore, had a more homogeneous patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted logistic regression was performed to analyse the variables associated with the presence of depression and anxiety during pregnancy, and the occurrence of postpartum depression and anxiety. Finally, binary logistic regression was performed to analyse the variables related to the manifestation of depression and anxiety during and after pregnancy, dichotomizing these variables according to the score equal to 75 on the SCL-90 test (Karlsson et al, 2021). Data were analyzed with SPSS Version 22.0.…”
Section: Sociodemographicmentioning
confidence: 99%
“…People with substance use problems report more frequent challenges linked to impulsivity, hyperactivity and inattention (IHI) than people without substance use problems [ 7 ]. Impulsivity is considered an etiological pathway to the development of SUD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity is considered an etiological pathway to the development of SUD [ 8 ]. People with higher levels of IHI are likely to have longer histories of substance use and greater mental distress [ 7 ]. Various conditions contribute to IHI and a portion of people who experience IHI are diagnosed with attention deficit hyperactivity disorder (ADHD), defined by ICD-11 as persistent “inattention and/or hyperactivity-impulsivity that has a direct negative impact on academic, occupational, or social functioning” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%